Delta Técnica: aplicação e criação de ferramentas de Business Intelligence e Analytics - Fragomeni Neto, Carlos (2021)
Subject: With the growth of the Internet and an even more significant number of technological devices being released every year, the volume of data is growing exponentially. As a result of this new reality, new tools for the organization of information were developed. These tools enable new ways to analyze information and increase organizations' intelligence. Application: This work presents the implementation of a new way to analyze historical data of jobs executed using tools that improve internal data analysis. Delta Técnica, a company specializing in road infrastructure, implemented this solution, in which, for the most, leaders used intuition in the decision-making process. Impact: Two surveys conducted measured an increase in perceptions of usefulness, handiness in use, and information quality among users of this technological solution, supporting Delta Técnica's partners' decision-making processes, in addition to other associated benefits. Innovation: The innovation in this project came from the solution. A new way of analyzing historical data was generated, which improved the information available to Delta Técnica's leadership. Complexity: Beyond the technical knowledge needed to integrate the databases and transform a large amount of data into information to Delta Técnica's partners, the support of the leadership and the technical team was essential to execute a project of this magnitude. Methodological method and procedure: The Methodology of Preparation of practical and applied work: administration and accounting, written by Marcondes, Miguel, Franklin & Perez (2017), was adopted.